1990
DOI: 10.1111/j.1600-0447.1990.tb01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual rhythms of violence in hospitalized affective patients: correlation with changes in the duration of the daily photoperiod

Abstract: We extensively reviewed the medical records of violent patients restrained in a locked psychiatric ward of a university-based hospital for 6 years (1980-1985). A total of 551 patients were restrained at least once during hospitalization, of which 186 patients had affective disorders and 365 had nonaffective psychiatric illnesses. While the number of restrained nonaffective patients was constant throughout the year, the number of restrained affective patients showed a circannual rhythm with nadirs in May and No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…We found a significant association between seasonality and clinical severity: as a matter of fact, the spring appears to be more burdened by hospitalizations motivated by suicide attempt and need for physical restraint (Reutfors et al 2009b) reported, in a study conducted in Sweden between 1992 and 2003 on schizophrenic patients, increased suicide rates in late spring and summer (May to August) with a peak in June. Lastly, few data are available in the literature concerning the prevalence of need for physical restraint and its relation to seasonality and photoperiod (Reitman et al 1990;Kaplan et al 1996;Wynn 1996); for instance, Wynn showed that there is a daily peak with most use of restraint in the afternoon and early evening and a seasonal peak-with the most use of restraint in autumn (Wynn 1996). Reitman and co-workers highlighted the importance of seasonality and photoperiod on 551 patients (186 with a diagnosis of affective disorders and 365 with non affective psychiatric illness); depicting a circannual rhythm with nadirs in May and November and peaks in June and December for restrained affective patients, while the number of restrained non affective patients was constant throughout the year (Reitman et al 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a significant association between seasonality and clinical severity: as a matter of fact, the spring appears to be more burdened by hospitalizations motivated by suicide attempt and need for physical restraint (Reutfors et al 2009b) reported, in a study conducted in Sweden between 1992 and 2003 on schizophrenic patients, increased suicide rates in late spring and summer (May to August) with a peak in June. Lastly, few data are available in the literature concerning the prevalence of need for physical restraint and its relation to seasonality and photoperiod (Reitman et al 1990;Kaplan et al 1996;Wynn 1996); for instance, Wynn showed that there is a daily peak with most use of restraint in the afternoon and early evening and a seasonal peak-with the most use of restraint in autumn (Wynn 1996). Reitman and co-workers highlighted the importance of seasonality and photoperiod on 551 patients (186 with a diagnosis of affective disorders and 365 with non affective psychiatric illness); depicting a circannual rhythm with nadirs in May and November and peaks in June and December for restrained affective patients, while the number of restrained non affective patients was constant throughout the year (Reitman et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, few data are available in the literature concerning the prevalence of need for physical restraint and its relation to seasonality and photoperiod (Reitman et al 1990;Kaplan et al 1996;Wynn 1996); for instance, Wynn showed that there is a daily peak with most use of restraint in the afternoon and early evening and a seasonal peak-with the most use of restraint in autumn (Wynn 1996). Reitman and co-workers highlighted the importance of seasonality and photoperiod on 551 patients (186 with a diagnosis of affective disorders and 365 with non affective psychiatric illness); depicting a circannual rhythm with nadirs in May and November and peaks in June and December for restrained affective patients, while the number of restrained non affective patients was constant throughout the year (Reitman et al 1990). This is in agreement with our results and those stated by Kaplan and coworkers (1996).…”
Section: Discussionmentioning
confidence: 99%
“…Peaks in Spring and Autumn have also been observed in the aggression of patients hospitalised for mental illness [Roitman et al, 1990]. Mental disorders, however, are not equally sensitive to seasonally based environmental cues.…”
Section: Chrono-epidemiology Of Violencementioning
confidence: 89%
“…Interestingly enough, the percentage of German patients restrained was reflective of their proportion in the city's population: 14.6% restrained and 14.4% living in the city, respectively.&dquo; A language barrier, therefore, could explain the increasing use of restraint on immigrants only if one assumes that German was more comprehensible to staff than English spoken with an Irish brogue. A disproportionately large number of immigrants were therefore restrained in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…While 8.2% of the patients were described as having suicidal tendencies, 14.8% of the incidents of restraint involved potential or actual 'injury to self'. The entry 'disposition to injure others' on an admission record did not prove to have predictive value, as one-half the patients who were restrained were described by the admitting physician as not violent.…”
Section: Discussionmentioning
confidence: 99%